2022
DOI: 10.1002/anse.202200085
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Sensing Chemiluminescent Iridium(III) 1,2‐Dioxetanes: Unusual Coordination and Activity

Abstract: Next generation chemiluminescent iridium 1,2-dioxetane complexes have been developed which consist of the Schaap's 1,2dioxetane scaffold directly attached to the metal center. This was achieved by synthetically modifying the scaffold precursor with a phenylpyridine moiety, which can act as a ligand. Reaction of this scaffold ligand with the iridium dimer [Ir-(BTP) 2 (μ-Cl)] 2 (BTP = 2-(benzo[b]thiophen-2-yl)pyridine) yielded isomers which depict ligation through either the cyclometalating carbon or, interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Kagalwala and co-workers used a piperazine linker to accomplish chemiluminescence resonance energy transfer to an iridium complex for ratiometric oxygen sensing . Recently, the same team also reported that a Suzuki coupling can be employed to directly link an iridium luminophore to the phenol unit to achieve highly efficient through bond energy transfer . We do note that efficiency of energy transfer between the excited state phenolate and appended fluorophore can be dependent on the precise molecular structure.…”
Section: Energy Transfer Cassettesmentioning
confidence: 76%
See 1 more Smart Citation
“…Kagalwala and co-workers used a piperazine linker to accomplish chemiluminescence resonance energy transfer to an iridium complex for ratiometric oxygen sensing . Recently, the same team also reported that a Suzuki coupling can be employed to directly link an iridium luminophore to the phenol unit to achieve highly efficient through bond energy transfer . We do note that efficiency of energy transfer between the excited state phenolate and appended fluorophore can be dependent on the precise molecular structure.…”
Section: Energy Transfer Cassettesmentioning
confidence: 76%
“…However, there has recently been a flurry of renewed research activity using chemiluminescent 1,2-dioxetanes for cellular and in vivo imaging following demonstrations that these molecules were biocompatible and had bright enough emission for use in whole animal imaging. Shabat and co-workers also introduced important structural modifications that increased quantum yield in aqueous systems without the need for polymeric encapsulation, , leading to improved applicability for bioanalysis and imaging. These innovations have enabled a new field of activity-based chemiluminescence imaging agents for analytes including galactosidase, phosphatase, proteases, tyrosinase, nitroreductase, ,, carboxyl esterase, H 2 S, , ONOO – , H 2 O 2 , , HNO, HOCl, formaldehyde, pH, , a genetically engineered esterase/ester pair, and O 2 , , to name a few. Central to advancing the capabilities of these types of 1,2-dioxetane imaging agents is understanding how modifications of the structural design impact the chemiluminescence properties including quantum yields, kinetics, and emission wavelengths. In this Perspective, we will do a selective survey of the landscape of triggerable 1,2-dioxetane structures and consider how their design features affect chemiluminescent properties.…”
mentioning
confidence: 99%
“…Two related chemiluminescent iridium (III) complexes (204) have also been developed, with complex 204b displaying an unusual sulfur ligation. 397 The direct conjugation of the 1,2-dioxetane scaffold to iridium(III) complexes allows more efficient energy transfer, giving rise to single red chemiluminescence. The cationic complex 204b has been used for in vivo chemiluminescence imaging due to its higher aqueous solubility.…”
Section: Chemiluminescence Imagingmentioning
confidence: 99%
“…New generation phenoxy 1,2-dioxetane-based chemiluminescent probes bearing electron-withdrawing acrylate units have attracted great attention in recent years as an alternative to fluorescent probes. [69][70][71][72][73][74][75][76][77] Chemiluminescent probes do not require external light irradiation to emit light and offer a very high signal-to-noise ratio along with a high selectivity and sensitivity. [78][79][80] Additionally, they bear a modular scaffold, which can be simply modified toward the development of activity-based probes.…”
Section: Introductionmentioning
confidence: 99%